Targeting cyst wall is an effective strategy in improving the efficacy of marketed contact lens disinfecting solutions against Acanthamoeba castellanii cysts - Abjani, Farhat; Khan, Naveed Ahmed *; Yousuf, Farzana Abubakar; Siddiqui, Ruqaiyyah Bano * (Elsevier, 2016)
Acanthamoeba cysts are highly resistant to contact lens disinfecting solutions. Acanthamoeba cyst wall is partially made of 1,4 β-glucan (i.e., cellulose) and other complex polysaccharides making it a hardy shell that protects the resident amoeba. Here, we hypothesize that targeting the cyst wall structure in addition to antiamoebic compound would improve the efficacy of marketed contact lens disinfecting solutions. Using chlorhexidine as an antiamoebic compound and cellulase enzyme to disrupt cyst wall structure, the findings revealed that combination of both agents abolished viability of Acanthamoeba castellanii cysts and trophozoites. When tested alone, none of the agents nor contact lens disinfecting solutions completely destroyed A. castellanii cysts and trophozoites. The absence of cyst wall-degrading enzymes in marketed contact lens disinfecting solutions render them ineffective against Acanthamoeba cysts. It is concluded that the addition of cyst wall degrading molecules in contact lens disinfecting solutions will enhance their efficacy in decreasing the incidence of Acanthamoeba effectively.